2004
DOI: 10.1515/cclm.2004.201
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and immunological analyses of patients with increased serum butyrylcholinesterase activity and its C5 variant form

Abstract: Recent evidence has denied genetic abnormality as a mechanism of the C5 variant of butyrylcholinesterase (BChE) and proposed the binding of an unknown protein with the C4 component. The present study aimed to evaluate whether the coding sequences and non-translated sequences of the BChE gene at exons 1 to 4, 3q are structurally different in subjects having elevated BChE with and without the C5 variant phenotype. We also attempted to identify the unknown protein associated with the C5 variant and measured the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Considering that the work of Akizuki et al. () suggested that there is no relationship between increased BChE activity which occurs in CHE2 C5+ and variants of the BCHE gene, since no association between BCHE gene variants and CHE2 C5+ phenotype was observed, we can suppose that the responsible for increased activity in intense CHE2 C5+ individuals would be the Lpd.…”
Section: Discussionmentioning
confidence: 83%
“…Considering that the work of Akizuki et al. () suggested that there is no relationship between increased BChE activity which occurs in CHE2 C5+ and variants of the BCHE gene, since no association between BCHE gene variants and CHE2 C5+ phenotype was observed, we can suppose that the responsible for increased activity in intense CHE2 C5+ individuals would be the Lpd.…”
Section: Discussionmentioning
confidence: 83%
“…A search through this region with current techniques would be time-consuming and expensive and not justified until the linkage result in this region has been replicated. One possibility that should be considered is that this region of chromosome 5 contains a gene for a protein that binds to cholinesterase and increases its activity (24 ); efforts to identify the nature of this protein by conventional biochemical means have been unsuccessful to date. Another possibility is that genes in this region affect the risk of insulin resistance and metabolic syndrome and that the linkage for cholinesterase activity is a consequence of this.…”
Section: Discussionmentioning
confidence: 99%
“…This occurs with a frequency of 8% to 10% among Europeans (22 ), and is ascribed to the effects of another gene, cholinesterase (serum), 2 (CHE2), whose location is uncertain (23 ). A recent report (24 ) has shown that the increased activity is not attributable to increased cholinesterase protein concentration, but rather to increased specific activity.…”
mentioning
confidence: 96%
“…92 , 93 These variants have the wild-type BCHE nucleotide sequence in their exons and promoter region. 93 Heritable quantitative trait loci have been identified in intron 2 and the 3′-UTR of the BCHE gene and on chromosome 5q, 6 but it is unknown whether mutations at these loci increase or decrease BChE activity levels. Additional loci that affect BChE activity have been identified by the genome-wide association scan method.…”
Section: Effect Of Bche Genetic Variants On Analysis Of Exposure To Omentioning
confidence: 99%